Evaluation of anti-hemagglutinin Hn-33 single domain antibodies: kinetics, binding epitopes, and thermal stability. (8th August 2011) - Anderson, George P.; Zabetakis, Dan; Bernstein, Rachael D.; Cai, Shuowei; Singh, Bal Ram; Goldman, Ellen R.
Botulinum Neurotoxin A (BoNT/A) is produced by Clostridium botulinum as a complex with Neurotoxin-Associated Proteins (NAPs) which protect the toxin from proteases and promote adsorption in the gut. Hemagglutinin 33 (Hn-33) makes up the largest fraction of NAPs in the BoNT/A complex. We characterised single domain antibodies (sdAb) which bind Hn-33; the dissociation constant (Kd) varied from 3.8 × 10 −9 M to 1.3 × 10 −10 M. Sandwich assays showed that the six sdAb bind two distinct epitopes on Hn-33. Circular dichroism was used to monitor sdAb's secondary structure, thermal denaturing upon heating and rapid refolding upon cooling.